The program management office advantage : a powerful and centralized way for organizations to manage projects - Tjahjana, Lia; Dwyer, Paul; Habib, Mohsin (American Management Association, 2009)
Already a best practice for the majority of Fortune 500 companies, Program Management Office (PMO) is being embraced by large and small organizations eager to efficiently manage all their projects. This helpful guide introduces readers to the business reasons for having a centralized project department and explains the PMO's functions and how to set up and run a PMO. Readers will find detailed information on selecting projects, conducting project health checks, providing program management training to the organization, creating and implementing a standardized program management process, and mo.